Analysis Of Potential Development of Fishery By-Product Processing Industry in Lingga Regency, Riau Islands Province - Wisman Indra Angkasa; Ida Royanti; Renny Primasari Gustia Putri; Citra Kusumaning Dyah; Dewi Nandyawati (Return : Study of Management, Economic and Bussines, 2022)
Background: Lingga Regency has a great potential for marine fishery products that about 96 % of its area is marine waters. However, it has not provided too much income for the region since this great potential has not been fully exploited. At least 1,728 tons of export quality of live and dead fish are sent to Singapore in a year. Unfortunately, the revenue of overall exported fish is received by Batam and Tanjung Pinang city, because it becomes the export access of Lingga fish products. One of the programs is the development of the Fishery Processing Industry to increase the added value of marine by-products by involving community participation Aim: The purpose of the study was to determine the potential for the development of a fishery by-product processing industry Method: Data collection techniques were observation, in-depth interviews and document review. The data analysis consists of the type and capacity of the industry, production time assumptions and utility. Findings: The results showed that Lingga Regency has the potential to develop a fishery by-product industry, especially a fish flour industry with a capacity of 1 ton per day, with a production time of 5.6 days in a week and 51 weeks in a year. The raw materials used for the industry was a waste from fish fillet and minced fish processing industry with both of yield were 35 %. The initial production capacity of this industry was set at 66% and will increase annually with a maximum used capacity of 89%.